ANALISIS BIAYA DAN WAKTU PADA PEMBANGUNAN GEDUNG TRAUMA CENTER DAN INTENSIVE CARE TAHAP IV RSUD DR. SOEDONO MADIUN DENGAN METODE EARNED VALUE (Jurnal Spesialis Teknik Sipil (JSpTS), 2021)
The earned value concept method can be used to analyze performance and estimate the achievement of goals. According to Auzan, et al (2017), there are three indicators in the concept of result value analysis, namely ACWP (Actual Cost of Work Performed) which is the actual cost of the work that has been carried out, BCWP (Budgeted Cost of Work Performed) which is a budget equal to the work performed. has been implemented, BCWS (Budgeted Cost of Work Schedule) is the amount of the budget for the planned work. In the research conducted on the Construction of the Trauma Center and Intensive Care Building Phase IV RSUD DR. SOEDONO Madiun, the data collection as research material was obtained from the implementing contractors and also some from the supervisory consultants. Time performance in the first week to week 7 (seven) obtained negative numbers for (SV) and (CV) meaning that the work was completed late and cost higher than the budget. While the value of SPI and CPI < 1, then the time performance is not good, meaning that the work is late from the planned schedule. The project performance is the same as the week 7 with a progress of -6.57%, the estimated cost required to carry out the project until it is completed is Rp. 64,938,243,717.90 means that there is a loss of Rp. 1,773,437,194.04 of the contract value. The estimated time for ETS (Estimate to Schedule) and EAS (Estimate at Schedule) until this project is completed (with a delay of –6.57% at week 7) are: ETS = 254 days = 36 weeks and EAS = 303 days = 44 weeks. So it can be concluded that if the project's performance is the same as the performance at the time of the review in week 7 of the planned 168 days or 24 weeks, it swells to 303 days or 44 weeks. This means almost double the planned time. performance at the time of review in